Recent advances in district energy systems: A review. (1st December 2020) - Mahmoud, Montaser; Ramadan, Mohamad; Naher, Sumsun; Pullen, Keith; Baroutaji, Ahmad; Olabi, Abdul-Ghani
Highlights: District energy systems are very efficient in reducing global energy consumption. Advanced district energy systems involve, co-generation, poly-generation and heat recovery. Control, optimization and energy storage are among the challenges that face the development of this domain. Abstract: World energy consumption has increased significantly in the last decade and for this reason several energy management strategies are currently under investigation to accommodate this high demand. In this frame, the current paper presents a review of the advances of district systems (DSs) which offers a contribution to the mission to reduce the environmental and economic impact of energy consumption. The aim of the study is to examine the potential of these systems and their ability to cope with the requirements of energy demands. Additionally, the paper reviews several optimization strategies including poly-generation, cogeneration and energy storage that could be adopted to upgrade the performance of DSs. Furthermore, the paper discusses the main obstacles facing the development of this domain and proposes some suggestions to encourage adoption of the district approach.